2007
DOI: 10.1111/j.1447-0756.2007.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ileus in a pregnant woman at term pregnancy accompanied by labor pains

Abstract: Intestinal obstruction in pregnancy is a rare, but serious complication of pregnancy with significant maternal and fetal mortality. We herein report a case of intestinal strangulation in a pregnant woman with a history of pelvic surgery due to an ectopic pregnancy. Epigastric pain occurred at term pregnancy with concomitant onset of labor pains. The epigastric pain disappeared transiently, and she gave a birth to a healthy child. However, the pain appeared again after the vaginal delivery. She immediately unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Kuwahata et al suggested that the rapid shrinking of the uterus after delivery and sudden changes in the posi- tion of the abdominal organs might induce ileal knotting. 7 The fact that our patient had no surgical history and was referred with epigastric pain at term probably masked the clinical picture of ileal knotting. Thus, it was considered as part of the process of labor, which may have triggered labor, followed by delivery.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Kuwahata et al suggested that the rapid shrinking of the uterus after delivery and sudden changes in the posi- tion of the abdominal organs might induce ileal knotting. 7 The fact that our patient had no surgical history and was referred with epigastric pain at term probably masked the clinical picture of ileal knotting. Thus, it was considered as part of the process of labor, which may have triggered labor, followed by delivery.…”
Section: Discussionmentioning
confidence: 91%
“…Mechanical bowel obstruction often occurs late in pregnancy, although it has been reported in puerperium. 7 Our patient's symptoms of MBO started at term of the gestation period, then disappeared transiently after delivery and appeared again at puerperium. We could not establish whether ileal knotting triggered labor or labor triggered ileal knotting and the ensuing events.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other causes include intussusception, hernia, and cancer [1]. Furthermore, the mortality rate of midgut volvulus in pregnancy is significantly higher (3–15%) with respect to the general population [13]. …”
Section: Discussionmentioning
confidence: 99%